The Handbook of English pronunciation - Reed, Marnie; Levis, John (John M.). (Chichester, West Sussex, UK Wiley-Blackwell, 2015)
"The Handbook of English Pronunciation presents a comprehensive exploration of the characteristics of English pronunciation, including language acquisition, English in the world, its relationship to modern technology, the shifting role of accent, and more"--Provided by publisher.
Machine generated contents note -- Table of Contents -- Notes on Contributors -- Introduction -- A. The History of English Pronunciation -- 1. The historical evolution of English pronunciation (Jeremy Smith, UK) -- 2. Accent as a social symbol (Lynda Mugglestone, UK) -- 3. History of ESL Pronunciation Teaching (John Murphy, US and Amanda Baker, Australia) B. Describing English Pronunciation -- 4. Segmentals (David Deterding, Brunei) -- 5. Syllable structure (Adam Brown, New Zealand) -- 6. Lexical stress in English pronunciation (Anne Cutler, The Netherlands) -- 7. The Rhythmic Patterning of English(es): Implications for Pronunciation Teaching (Ee Ling Low, Singapore) -- 8. English Intonation - Form and Meaning (Anne Wichmann, UK and John Levis, US) C. Pronunciation and Discourse -- 9. Connected speech (Ghinwa Alameen, Syria and John Levis, US) -- 10. Functions of intonation in discourse (Anne Wichmann, UK) -- 11. Pronunciation in the analysis of discourse (Beatrice Szczepek Reed, UK) -- 12. Fluency (Ron Thomson, Brock University, Canada) D. Pronunciation of the major varieties of English -- 13. North American English (Charles Boberg, Canada) -- 14. British English (Clive Upton, UK) -- 15. Australian/New Zealand English (Laurie Bauer, New Zealand) -- 16. The Pronunciation of English in South Africa (Ian Bekker, Zambia and Albertus van Rooy, Zambia) -- 17. Indian English Pronounciation (Pramod Pandey, India) -- 18. Pronunciation and World Englishes (Cecil Nelson, US and Seong-Yoon Kang, South Korea) E. Pronunciation and language acquisition -- 19. The acquisition of the English Sound System (Marilyn Vihman, UK) -- 20. Variables affecting L2 pronunciation development (Pavel Trofimovich, Sara Kennedy, Jennifer Anne Foote, Canada) F. Pronunciation Teaching -- 21. Intelligibility in Research and Practice: Teaching Priorities (Tracey Derwing and Murray Munro, Canada) -- 22. The Segmental/Suprasegmental Debate (Beth Zielinski, Australia) -- 23. Applying theories of learning and language to teaching pronunciation (Graeme Couper, New Zealand) -- 24. The pronunciation of English as a Lingua Franca (Robin Walker, Spain and Wafa Zoghbor, UAE) -- 25. Intonation in research and practice: The importance of metacognition (Marnie Reed and Christina Michaud, US) -- 26. Integrating pronunciation into the language classroom (Isabelle Darcy and Laura Sicola, US) -- 27. Using orthography to teach pronunciation (Wayne Dickerson, US) -- 28. Technology and learning pronunciation (Rebecca Hincks, Sweden) -- Index.
Includes bibliographical references and index.
Keywords: English language -- Pronunciation -- Handbooks, manuals, etc